2012
DOI: 10.1159/000341384
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Analysis in the ADEBAR Trial: Sequential Anthracycline-Taxane Therapy Compared with FEC120 for the Adjuvant Treatment of High-Risk Breast Cancer

Abstract: Background: Data from meta-analyses have shown taxane-containing therapies to be superior to anthracycline-based treatments for high-risk breast cancer. Patients and Methods: The ADEBAR trial was a multicenter phase III trial in which patients with lymph node-positive breast cancer were prospectively randomized for either sequential anthracycline-taxane or FEC120 therapy. Patients received 4× epirubicin (90 mg/m2) and cyclophosphamide (600 mg/m2) every 3 weeks (q3w), followed by 4× doceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The higher risk of recurrence and mortality in obese patients could be related to a lesser efficacy of anti-cancer treatments probably due to plasma adipokine variations linked to overweight. Indeed, obese breast cancer women are less sensitive to chemotherapy [ 12 ] and present higher mortality rates [ 13 15 ]. MDA-MB-231 mammary cancer cells treated with adipose stem cell supernatants present resistance to doxorubicin [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The higher risk of recurrence and mortality in obese patients could be related to a lesser efficacy of anti-cancer treatments probably due to plasma adipokine variations linked to overweight. Indeed, obese breast cancer women are less sensitive to chemotherapy [ 12 ] and present higher mortality rates [ 13 15 ]. MDA-MB-231 mammary cancer cells treated with adipose stem cell supernatants present resistance to doxorubicin [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies 31,38 examined drugs not commonly used in Canada for the treatment of breast cancer. Several studies 53,54,[56][57][58] used the fec regimen with or without taxanes and with doses of epirubicin less than 100 mg/m 2 ; they are thus not relevant to practice in Ontario. A few publications presented trial subgroup analyses or molecular studies.…”
Section: Antimetabolites and Anthracyclinesmentioning
confidence: 99%
“…In the present evidence review, trials of taxanes represented the largest number of rcts (fifty-five trials in ninety-three publications) and are summarized in Supplemental Table 3 21,27-30,35,36, [49][50][51][52][53][54] . Because taxane studies are relatively recent, our database search found most of the published trials cited in other reviews or meta-analyses.…”
Section: Taxanesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Dooley et al, 2017) that add to their fear of recurrence (Miroševič et al, 2019). In recent years, other factors, such as tumor grade, estrogen receptor, and progesterone receptor status, HER2 overexpression, and, in some cases, genomic profiles, have been added to the prognostic value of TNM staging based on tumor size (T), number of regional lymph nodes affected (N), and the presence or absence of distant metastases (M), yielding more robust and precise prognostic information (Schönherr et al, 2012;Piñeros et al, 2019). Physicians estimate risk of adjuvant treatment-associated toxicity on the rates of side effects reported in clinical trials.…”
Section: Introductionmentioning
confidence: 99%